2019
DOI: 10.1016/j.isci.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Asymmetric Hydrogenation of Cyclic Sulfamidate Imines: Efficient Synthesis of Chiral Cyclic Sulfamidates

Abstract: Summary Chiral cyclic sulfamidates are useful building blocks to construct compounds, such as chiral amines, with important applications. Often these compounds can only be generated through expensive precious metal catalysts. Here, Ni(OAc) 2 /( S , S )-Ph-BPE-catalyzed highly efficient asymmetric hydrogenation of cyclic sulfamidate imines was successfully developed, affording various chiral cyclic sulfamidates with high yields and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 114 publications
1
11
0
1
Order By: Relevance
“…The heterolytic cleavage of the H-H bond is believed to be more facile than the homolytic oxidative addition that results in Rh dihydride. Similar effect has been proposed for Co 23 , Ni 34 , and Ru 35 catalysts. Ligand exchange between 2F and the enamine results in the formation of the Rh hydride amine complex iii that can undergo hydride transfer to the unsaturated C=C bond.…”
Section: Resultssupporting
confidence: 83%
“…The heterolytic cleavage of the H-H bond is believed to be more facile than the homolytic oxidative addition that results in Rh dihydride. Similar effect has been proposed for Co 23 , Ni 34 , and Ru 35 catalysts. Ligand exchange between 2F and the enamine results in the formation of the Rh hydride amine complex iii that can undergo hydride transfer to the unsaturated C=C bond.…”
Section: Resultssupporting
confidence: 83%
“…In view of current interest in the development of earthabundant metal catalysts in asymmetric hydrogenation [31][32][33][34][35][36][37][38][39][40][41] , which are inexpensive and environmentally friendly, the use of nickel has drawn increasing attention 24,[31][32][33][34][35][36][37][38][39][40][41] . Although Nicatalyzed asymmetric reduction has seen rapid development, the asymmetric hydrogenation of imines is still in its infancy 24,[42][43][44] . To date, only a few Ni-catalyzed asymmetric hydrogenations of imines have been reported by Zhang 24,43,44 and our group 42 , and the imines substrates are all activated by N-sulfonyl groups (Fig.…”
mentioning
confidence: 99%
“…Although Nicatalyzed asymmetric reduction has seen rapid development, the asymmetric hydrogenation of imines is still in its infancy 24,[42][43][44] . To date, only a few Ni-catalyzed asymmetric hydrogenations of imines have been reported by Zhang 24,43,44 and our group 42 , and the imines substrates are all activated by N-sulfonyl groups (Fig. 1c).…”
mentioning
confidence: 99%
“…Focusing on the substrate scope it was found that substituted phenyl groups affords improved results in some cases and enantioselectivities of 83-99%. 44 Diphosphine ligand 2 was also found to be effective in the Pd-catalysed AH of sulfonyl imines. The system proved effective under a low hydrogen pressure and in the presence of Lewis acids.…”
Section: Organic Chemistry Frontiers Reviewmentioning
confidence: 99%